About the geometrical properties of the root condition for the third order polynomials - Štikonas, Artūras (Lietuvos matematikos rinkinys, 1999)
This paper deals with a root condition for polynomial of the second and third order. We prove the root criterion for such polynomial with complex coefficients and find regions for the root condition in the special coefficients’ phase space.